What is the Next Step after an Electrodiagnostic Study in Children with Polyneuropathies? Rationale for Laboratory and Other Diagnostic Tests: Approach to children peripheral neuropathy. - babaee, marzieh; Urtizberea, J.Andoni; Fatehi, Farzad; Rayegani, Seyed Mansoor (Iranian Journal of Child Neurology, 2023)
The etiology of polyneuropathies varies in the pediatric population, where hereditary or metabolic disorders are far more common than in adults. However, treatable polyneuropathies, also prevalent in these settings, are those to prioritize. Moreover, diagnosing subacute and chronic symptoms in children can be challenging compared to adults. Therefore, selecting the best and most relevant laboratory investigations and paraclinical studies is critical. This taskcan be relatively challenging in countries with limited resources or insurance coverage. This study describe the various types of polyneuropathies found in children and their characteristics and suggest an algorithm for using the best laboratory tests in the context of the Iranian healthcare system.